Is leisure research contributing to sustainability? A systematic review of the literature. Issue 3 (3rd July 2017) - Vaugeois, Nicole; Parker, Pete; Yang, Yufan
ABSTRACT: The purpose of this study was to identify and summarize to what extent articles in leisure journals have focused on and critically examined the relationship between leisure and sustainability. The study was conducted using content analysis of articles in leisure journals over the past decade (2005–2015) including: Leisure/Loisir, Journal of Leisure Research, Leisure Studies, Leisure Sciences, World Leisure, Journal of Park and Recreation Administration, Annals of Tourism Research, Journal of Sustainable Tourism, Journal of Travel Research, Tourism Management and Journal of Ecotourism . The results indicate that while some contributions to advance sustainability are emerging in leisure journals, there is a need for more explicit links between leisure and sustainability in the literature. The paper highlights areas where leisure research could be making stronger contributions to advance sustainability moving forward including questioning the relationship between leisure and sustainability, determining the level of sustainability of the leisure industry and proposing and monitoring new models and approaches to enhance sustainability.